The Problem of Social Time in the Sociology of Classic Period - Ambarova, Polina (Visnyk of V. N. Karazin Kharkiv National University. Series Sociological studies of contemporary society: methodology, theory, methods, 2019)
The article considers the problem of social time in the framework of the three paradigms of classical sociology – positivism, marxism and evolutionism. Three problems of social time identified and developed by prominent sociologists – A. Comte, G. Spencer, E. Durkheim, K. Marx – are presented in the paper. The author defines the problems of the dynamics of social time, the subject of social time, as well as the mechanisms of transfer of social experience. The continuity of approaches to the study of social time between sociology of the classical stage and the philosophy of the Enlightenment epoch is justified. In the article it is proved that at this stage the problem of social time was not considered separately from other problems, it was inherently included in the analysis of the regularities of society development, mechanisms of maintenance of its integrity, urgent problems of the economic functioning of the capitalist society of that time. At the same time it is shown that at this stage of the development of sociology the key problems and methodological principles of research of the phenomenon of social time were already formulated and perceived and developed by subsequent generations of sociologists.